Aromatic thiol-mediated cleavage of N–O bonds enables chemical ubiquitylation of folded proteins - Caroline E. Weller (Nature Portfolio, 2016)
Chemical approaches to site-specifically ubiquitylate a target protein allow investigation of the biochemical effects of this modification, but they often destabilize the protein. Here, the authors report on a synthetic conjugation strategy that leads to protein ubiquitylation in non-denaturing conditions.